Делчев во македонскиот код на драмскиот текст - Мојсова-Чепишевска, Весна; Антоновски, Иван (Институт за национална историја, Универзитет „Св. Кирил и Методиј“ во Скопје, 2023)
The paper analyzes the presence of Goce Delchev in the Macedonian dramaturgy, from the beginning of the Macedonian contemporary teather to postmodernism, with the conclusion that it is the one of the dominants of the Macedonian code in the drama text. Delcev’s presence in Macedonian dramaturgy dates back to 1903, when on the occasion of his death, Vojdan Chernodrinski dedicated to him the drama/scene “Sreshta” – the first Macedonian operetta, after which it continued in the period between the two World Wars especially through the dramas dedicated to the Ilinden Uprising, following after the Second World War when the first Macedonian opera was dedicated to him, so he is also present in the nineties with Goran Stefanovski’s postmodernist works. Simultaneously, the text also comments on film and TV drama productions in which Delchev’s character is present. The text determines a division into two major periods related with the manner in which Delchev is present in the Macedonian dramaturgy. The first, it is a period in which Delchev is present a character behind the scene, a character which is recognized as an initiator and/or an inspirer of the work or the action or for some of the characters – a character-palimpsest or a character-hypertext, with presence that is (only) sensed. The second one, it is a period in which Delchev appears as a central, full-fledged character in literary and theatrical sense, and already with the Goran Stefanovski work as a main character, at the same time he is a character-protagonist and character-antagonist, completely abandoning the romantic notion. Considering drama as a key indicator of Macedonian cultural aesthetics, the paper states that Delchev is not only myth-hero, but also hero-cultural code and hero-cultural conscience.
150 години од раѓањето на Гоце Делчев: прилози од научната конференција одржана во Скопје на 3-4 мај 2022 год.
Делови од текстот се објавени и електронски, на порталот „Умно“: https://umno.mk/delchev-vo-makedonskiot-kod-na-dramskiot-tekst/
Keywords: Goce Delchev, Macedonian code, drama, literary history, cultural aesthetics, operetta, opera